Systematic Literature Review of Social Entrepreneurship Phenomenon: Perspectives and Theoretical Lenses - WAQAR, AMBER; FADZIL, AHMAD FIRDAUSE MD; JAMIL, MAHWISH; YAACOB, MOHD RAFI (The journal of contemporary issues in business and government, 2021)
Social entrepreneurship (SE) is an emerging subject in the field of entrepreneurship research since previous years. However, there has been a significant increase in social entrepreneurship research based on multifaceted literature reviews. Still, this field required more research to mature the concept of social entrepreneurship studies with different dimensions. The established SE literature shows a lack of studies classifying this phenomenon through the theoretical and practical lenses. The current study fills the gap by studying practical and theoretical perspectives of social entrepreneurship. This study used a systematic review spanning 2010 to 2020 to understand social entrepreneurship conceptual and theoretical perspectives. Based on the study findings, poverty reduction, economic growth, social innovation, job creation, and social entrepreneurship orientation is the cluster of social entrepreneurship. This study also describes few theories that explained the social entrepreneurship phenomenon, e.g. social capital theory, institutional theory, economic innovation theory, complex and ecosystem theory, holistic theory of individual decision making, and behavioural entrepreneurship theory in different perspectives; despite these theories, a multidimensional theoretical perspective needs to be discussed to explain social entrepreneurship comprehensively. Moreover, future directions are also suggested in this study to fill the potential in this field.